Blood Stain Removal: A Chemical Perspective on Set Stain - Azeez Mutiu O, (Chemistry and Biochemistry: Research Progress Vol. 6, 2025)
In healthcare laundry and linen processing, blood stain has been among the major stains encountered during operations. Laundry processors find it difficult to remove blood stains from the linens if allowed to stay for a certain period. However, a fresh blood stain may easily be removed with water at room temperature without application of any chemical or bleach during flush operation or break bath. When blood stain becomes set, removal or treatment seems to be cumbersome on the linen. The extent of the difficulty depends on the fibre composition of the linen or fabric. Blood stains adherence to textile materials or fabrics or hospital linen has been among the major challenging stains, aside from dye migration from one textile to another. There are many stain removal products developed to deal with these problems by different chemical companies globally. All these products have their adverse effects on the properties of the textile fibres that compose the material. The objective of the study is to eliminate the problem of blood stains in human endeavours, especially in laundry processing and healthcare facilities. For instance, chlorine bleach or oxalic acid can cause tendering of cellulosic fibre like cotton. To remove blood stains, it requires understanding the basic chemistry of blood and its constituents. Therefore, other potential stain removals used in this study include: water, detergent, oxalic acid, sodium hydroxide, and alkaline sodium hydrosulfite. Method of data analysis involved the evaluation of blood stained fabric sample after treatment through physical comparison of the degree of whiteness obtained with the original white sample (control sample). It was found that sodium hydroxide gave significant removal of the stain, followed by alkaline sodium hydrosulphite, while the rest did not show any significant removal. Furthermore, it can be concluded that sodium hydroxide at 5% concentration or below can effectively remove set blood stain provided the stained textile material has not been previously treated with any stain removal.